Novel approaches and perspectives in allergen immunotherapy - Hoffmann, Hans Jürgen; Pfaar, Oliver (Allergy, 2017)
In this review, we report on relevant current topics in allergen immunotherapy (AIT) which were broadly discussed during the first Aarhus Immunotherapy Symposium (Aarhus, Denmark) in December 2015 by leading clinicians, scientists and industry representatives in the field. The aim of this symposium was to highlight AIT-related aspects of public health, clinical efficacy evaluation, mechanisms, development of new biomarkers and an overview of novel therapeutic approaches. Allergy is a public health issue of high socioeconomic relevance, and development of evidence-based action plans to address allergy as a public health issue ought to be on national and regional agendas. The underlying mechanisms are in the focus of current research that lays the ground for innovative therapies. Standardization and harmonization of clinical endpoints in AIT trials as well as current knowledge about potential biomarkers have substantiated proof of effectiveness of this disease-modifying therapeutic option. Novel treatments such as peptide immunotherapy, intralymphatic immunotherapy and use of recombinant allergens herald a new age in which AIT may address treatment of allergy as a public health issue by reaching a large fraction of patients.